2021
DOI: 10.3389/fmicb.2021.681953
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Chili Monoculture Alters Environmental Variables Affecting the Dominant Microbial Community in Rhizosphere Soil

Abstract: Graphical AbstractLong-term chili monoculture alters environmental variables affecting the dominant microbial community in rhizosphere soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The continuous cropping barriers are considered the phenomenon in which after the soil was continuously planted with the same or related crops for a long time, the growth of the crop was weakened even under normal conditions of management, resulting in reduced production and quality ( Gao et al, 2019 ; Chen et al, 2021 ). Wine grapes, a crop with a high economic value and a long cultivation period with continuous cropping, are typical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous cropping barriers are considered the phenomenon in which after the soil was continuously planted with the same or related crops for a long time, the growth of the crop was weakened even under normal conditions of management, resulting in reduced production and quality ( Gao et al, 2019 ; Chen et al, 2021 ). Wine grapes, a crop with a high economic value and a long cultivation period with continuous cropping, are typical.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of continuous cropping of wine grapes regarding their associated microorganisms were primarily achieved through the assimilation and transformation of nutrients and the secretion of metabolites during plant growth ( Zhang C. et al, 2019 ; Chen et al, 2021 ). The alteration in the resident soil microflora has been widely associated with variations in the physicochemical properties of soil, SEA, and crop type ( Zhang et al, 2016 ; Liu et al, 2021 ; Fan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to increased levels of acidic ions (NO 3 − , SO 4 2− , Cl − , etc. ), which gradually acidify the soil [32,33]. The findings of a recent study indicated that the decrease in soil pH may be related to the secretion of more acidic substances by the root system during Eucalyptus growth [6].…”
Section: Influence Of Plantation Age On Nutrient Content Of Soilmentioning
confidence: 99%
“…It was shown that ALP activity increased significantly with a significant decrease in AP in continuous pure Eucalyptus stands. This phenomenon can be elucidated by the limitation of phosphorus nutrients, since microorganisms limited by a particular nutrient excrete the corresponding enzyme to acquire this resource [61]. Related studies have demonstrated that soil microorganisms promote the expression and activities of corresponding nutrient-acquiring enzymes during nutrient limitation, which in turn increases the enzyme activity when soil nutrient availability is reduced [60].…”
Section: Activity Of Soil Enzymes In Response To Different Transforma...mentioning
confidence: 99%